2017
DOI: 10.1039/c6nj03635j
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of electropolymerization of nickel(ii) salen type complexes

Abstract: Ni(II) complexes with (AE)-trans-N,N 0 -bis(salicylidene)-1,2-cyclohexanediamine ([Ni(salcn)]), and its methyl ([Ni(salcn(Me))]) and tert-butyl ([Ni(salcn(Bu))]) derivatives have been synthesized. Anodic electropolymerization has been used to form electrodes modified by polymer films. FTIR and FTIR ATR methods showed that the obtained films consist of polymers of phenyl-phenyl type. The structure of poly[Ni(salcn)] is built with 1,2,4-and 1,2,3,5-substituted chains. A three-step process of the oxidation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 76 publications
6
44
0
Order By: Relevance
“…Polymers were obtained by anodic electropolymerization using cyclic voltammetry. Curves were recorded in solutions of complexes (10 −3 mole·dm −3 ) in CH 2 Cl 2 /TBAH (0.1 mole·dm −3 ), at scan rates of 0.005–0.5 V·s −1 in positive potential ranges (0–1.6 V), involving two-step oxidation of complexes [ 35 , 37 ]; 1 to 20 electropolymerization cycles were recorded. As a result of the electropolymerization process, yellow electroactive, well adhering to the electrode surface polymer films, were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers were obtained by anodic electropolymerization using cyclic voltammetry. Curves were recorded in solutions of complexes (10 −3 mole·dm −3 ) in CH 2 Cl 2 /TBAH (0.1 mole·dm −3 ), at scan rates of 0.005–0.5 V·s −1 in positive potential ranges (0–1.6 V), involving two-step oxidation of complexes [ 35 , 37 ]; 1 to 20 electropolymerization cycles were recorded. As a result of the electropolymerization process, yellow electroactive, well adhering to the electrode surface polymer films, were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Our research presents electrodes modified with polymers of Ni (II) complexes with (±)- trans -N,N′-bis(salicylidene)-1,2-cyclohexanediamine ( poly [Ni(salcn)]) and its tert -Bu derivative, substituted in ortho positions of phenolate moieties ( poly [Ni(salcn(Bu))]). In previous studies, we have shown that they are conductive polymers [ 35 ]. They oxidize in two steps to the macro phenoxyl radical and macro bisphenoxyl radical [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of NiSalens in solution proceeds via three consequent oxidation steps . The potential applied is high enough to ensure the oxidation of the phenolate moiety to the Ni(II)‐phenoxyl radical complex (I oxidation step, E pa (I step) =0.7 – 1.2 V for different Salen‐type complexes) and then the oxidation of the Ni(II)‐phenoxyl radical complex to the Ni(II)‐bis‐phenoxyl radical complex (II oxidation step, E pa (II step) =1.1 – 1.4 V, depending on ligand structure) . Completion of these oxidation steps assures the possibility of the follow‐up reactions (dimerization and polymerization), regardless of the nature of the substituent affecting the reactivity of the radicals, thus making the synthetic protocol most universal.…”
Section: Resultsmentioning
confidence: 99%
“…Completion of these oxidation steps assures the possibility of the follow‐up reactions (dimerization and polymerization), regardless of the nature of the substituent affecting the reactivity of the radicals, thus making the synthetic protocol most universal. At the same time the applied potential is low enough to prevent the unwanted formation of Ni(II)‐phenoxonium cation form in solution (III oxidation step, E pa (III step) > 1.6 V), which can terminate the oligomerization of the complexes. In the papers cited above, the potentials were measured vs .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation